Atividade da paromomicina "in vitro" contra isolados clínicos de "Leishmania spp." e sua eficácia "in vivo" no tratamento da leishmaniose tegumentar : Activity of paromomycin "in vitro" against brazilian clinical isolates of "Leishmania spp." and its efficacy "in vivo" on treatment of experimental tegumentary - Coser, Elizabeth Magiolo, 1996- (2020)
Orientador: Adriano Cappellazzo Coelho